If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + -10 = -52 Reorder the terms: -10 + p = -52 Solving -10 + p = -52 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + p = -52 + 10 Combine like terms: -10 + 10 = 0 0 + p = -52 + 10 p = -52 + 10 Combine like terms: -52 + 10 = -42 p = -42 Simplifying p = -42
| f-92=7 | | p+0.5=-0.9 | | 4=w+-13 | | f-7=2 | | 3x-5+4x+10+x-5=180 | | br-bs= | | -9=9+v | | 4x=2x+4y | | 61=c+54 | | a/.5=2 | | v+-10=-5 | | 17=u-16 | | Y-4=-1x+3 | | 59=5y-11 | | 180=30+123+b | | 9=n+4 | | 2x+4+6X=-68 | | 9=2+4 | | 180=(16x-3)+45 | | 38=6x+6x-10 | | 29=6 | | -11=p-17 | | 4x-6+5x=57 | | 9=3g | | 180=16x-3+45 | | 5x+1-2x=27 | | 0.75y=2x-6 | | 2(y+2)-8=0 | | -4x^2+19x=-320 | | x+1-4x=13 | | 5/8q=-20 | | 8x-13y=12 |